2020
DOI: 10.3390/nu12040885
|View full text |Cite
|
Sign up to set email alerts
|

Parental Concerns about Child and Adolescent Caffeinated Sugar-Sweetened Beverage Intake and Perceived Barriers to Reducing Consumption

Abstract: Sugar-sweetened beverage (SSB) consumption contributes to obesity and chronic disease. SSB intake in children and adolescents remains well above recommendations and reducing intake is challenging. In addition to high sugar content, SSBs are the predominant source of caffeine among youth. However, whether caffeine in SSBs presents unique barriers to reducing consumption is unknown. Herein, we examine parental concerns about child caffeinated-SSB (CSSB) intake and describe parent-reported barriers to lowering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…Signs of addiction have also been reported among children in response to frequent SSB consumption (13,14). In our qualitative study (14), parents of children 8-17 years old reported that children experienced physical and affective withdrawal symptoms when caffeinated SSB intake was restricted. Similarly, Falbe et al (13) reported that adolescents, who reported habitual SSB consumption, regardless of whether SSBs were caffeinated or caffeine-free indicated increased SSB cravings and headaches, and decreased motivation, contentment, concentration, and wellbeing during 72 h of SSB cessation.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Signs of addiction have also been reported among children in response to frequent SSB consumption (13,14). In our qualitative study (14), parents of children 8-17 years old reported that children experienced physical and affective withdrawal symptoms when caffeinated SSB intake was restricted. Similarly, Falbe et al (13) reported that adolescents, who reported habitual SSB consumption, regardless of whether SSBs were caffeinated or caffeine-free indicated increased SSB cravings and headaches, and decreased motivation, contentment, concentration, and wellbeing during 72 h of SSB cessation.…”
Section: Introductionmentioning
confidence: 65%
“…Children who demonstrate more signs of addiction in their highly processed food consumption are more likely to have higher reward drive for food and higher body mass index (12). Signs of addiction have also been reported among children in response to frequent SSB consumption (13,14). In our qualitative study (14), parents of children 8-17 years old reported that children experienced physical and affective withdrawal symptoms when caffeinated SSB intake was restricted.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations